Echo-Doppler determinants of outcomes in patients with unoperated significant mitral regurgitation in current era. Issue 2 (1st August 2016) - Rafique, Asim M; Zarrini, Parham; Singh, Nirmal; Beigel, Roy; Tadwalkar, Rigved; Chonde, Meshe; Slipczuk, Leandro; Cercek, Bojan; Kar, Saibal; Siegel, Robert J
Abstract : Objective: One-half of patients with severe symptomatic mitral regurgitation (MR) do not undergo surgery due to comorbidities. We evaluated prognosticators of outcomes in patients with unoperated significant MR. Methods: In this observational study, we retrospectively evaluated medical records of 75 consecutive patients with unoperated significant MR. Results: All-cause mortality was 39% at 5 years. Non-survivors (n=29) versus survivors (n=46) were: older (77±9.8 vs 68±14, p=0.006), had higher New York Heart Association (NYHA) class (2.7±0.8 vs 2.3±0.8, p=0.037), higher brain natriuretic peptide (1157±717 vs 427±502 pg/mL, p=0.024, n=18), more coronary artery disease (61% vs 35%, p=0.031), more frequent left ventricular ejection fraction <50% (20.7% vs 4.3%, p=0.026), more functional MR (41% vs 22%, p=0.069), higher mitral E/E ′ (12.7±4.6 vs 9.8±4, p=0.008), higher pulmonary artery systolic pressure (PASP; 52.6±18.7 vs 36.7±14, p <0.001), more ≥3+ tricuspid regurgitation (28% vs 4%, p=0.005) and more right ventricular dysfunction (26% vs 6%, p=0.035). Significant predictors of 5-year mortality were PASP (p=0.001) and E/E ′ (p=0.011) using multivariate regression analysis. Conclusions: Patients with unoperated significant MR have high mortality. Elevated PASP and mitral E/E ′ were the most significant predictors of 5-year survival in patients with unoperated significant MR. Current American College of Cardiology (ACC)/American Heart Association (AHA) guidelines provide a limited incorporation of echo-Doppler parameters in the preoperative risk stratification of patients with severe MR.